PENGARUH KOMPENSASI DAN KEPEMIMPINAN TERHADAP TRUNOVER INTENTION - Wilda Mallawi; Muhammad Kasran; Suparni Sampetan (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to determine the effect of compensation and leadership on turnover intention in plywood company employees in South Sulawesi (South Sulawesi). In collecting data, the authors used the accidental sampling method with a sample of 100 respondents (employees). This research has been tested using an instrument test, classical assumption test, hypothesis test, and multiple linear regression test using SPSS 22.0 program. The results of the first test are that compensation has a negative effect on the turnover intention by calculating tcount (-0.768) < ttable (-1.985). The Company needs to pay more attention to the implementation of this compensation program seriously so that employees stay last longer at the plywood company. In the second test, the current pattern of leadership does not significantly affect turnover intention by calculating tcount (1.299) < ttable (1.985). Therefore leaders in the plywood company should change the leadership patterns to adjust the character of employees owned so that good synergies are built to foster comfort Work.